DIAGNOSIS OF RABBIT EIMERIOSIS IN QO‘SHTEPA AND TOSHLOQ DISTRICTS - N.T, Axmadaliyev; R.B, Davlatov (Research Focus International Scientific Journal, 2026)
This article presents the results of examinations for eimeriosis in rabbits kept on farms specializing in modern rabbit breeding in the Qo‘shtepa and Toshloq districts of Fergana region. In addition, the essence of the methods used for the examination is presented, complete information on the methods of conducting the examination is provided, and information on the extensiveness and intensity of invasion in farms in the districts is given.